2018
DOI: 10.1002/jper.18-0289
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori gastritis and dental diseases: A cross‐sectional, hospital‐based study in Eastern Saudi Arabia

Abstract: Background There is inconsistent evidence about the association between Helicobacter pylori (H. pylori) and dental diseases with possible effect of environmental factors. The aims of the study were to assess (1) the association between gastric and oral H. pylori colonization and (2) the association between oral colonization of H. pylori and dental diseases. Methods A cross‐sectional study was conducted in King Fahad University hospital in Khobar, Eastern Saudi Arabia in 2017. Patients admitted to the Endoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(82 reference statements)
1
4
0
1
Order By: Relevance
“…Today, many modifications of PCR technology have been developed to increase the sensibility of detection, even to increase sensitivity to 100% ( 61 ). In recent years, a new PCR system has been developed, which uses primer sets specific to 48 H. pylori strains in order to increase the diagnostic accuracy of PCR in the oral cavity; however, despite being a highly sensitive method, certain authors have drawn attention to its poor ability to detect small amounts of bacteria, depending on the specificity and sensitivity of the primer used, for example, primers related to bacterial urease activity often prove to be a confounding factor ( 62 ). Amiri et al ( 63 ) described a highly specific and sensitive DNA amplification method for the detection of H. pylori in dental plaque samples, showing that it had a higher detection rate than PCR by 66.67 and 44%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Today, many modifications of PCR technology have been developed to increase the sensibility of detection, even to increase sensitivity to 100% ( 61 ). In recent years, a new PCR system has been developed, which uses primer sets specific to 48 H. pylori strains in order to increase the diagnostic accuracy of PCR in the oral cavity; however, despite being a highly sensitive method, certain authors have drawn attention to its poor ability to detect small amounts of bacteria, depending on the specificity and sensitivity of the primer used, for example, primers related to bacterial urease activity often prove to be a confounding factor ( 62 ). Amiri et al ( 63 ) described a highly specific and sensitive DNA amplification method for the detection of H. pylori in dental plaque samples, showing that it had a higher detection rate than PCR by 66.67 and 44%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we analyzed the relationship between H. pylori infection and dental problems in people exposed to Pb and Cd, and found that the greater the numbers of FT and MFT are, the stronger the correlation between FT, MFT, and H. pylori infection is. Previous studies have not reached a consistent conclusion on the relationship between H. pylori infection and dental problems [17,37,40,41]. For example, Zahedi et al reported an association between gastric infection with H. pylori and the The Decayed, Missing, and Filled Teeth (DMFT) index [41].…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results have been reported on the association between dental problems, including missing teeth (MT), filled teeth (FT), missing or filled teeth (MFT), and H. pylori infection. Alag et al found that the number of MT does not seem to be associated with gastric or oral H pylori positivity [17]. In contrast, Shimoyama et al found that H. pylori infection was associated with a decreased risk of tooth loss in healthy Japanese men [18].…”
Section: Introductionmentioning
confidence: 99%
“…These findings conclude that developing new therapies and reducing periodontitis might decrease the risk of developing gastric Hp -related diseases. In contrast to these studies, one clinical-based study in Saudi Arabia, performed on 120 participants with good oral hygiene practices, showed that there was no significant association between gastric or oral Hp infection and periodontal disease [ 36 ]. In the present study, it is worth mentioning that periodontitis, with or without comorbidity, increases the risk of gastric Hp and, thereby, might be involved in the development and progression of many gastro-intestinal-related pathologies.…”
Section: Discussionmentioning
confidence: 99%